The Evaluation of Leadership Styles and their Effects on Employee Attitude: Evidence from a Manufacturing Company in South Eastern Nigeria - Jalloh, Abdulai Alpha; Nwogbo, Ifeanyi Emmanuel; Nwosu, Laurine Chikodiri; Onyibe, Priscillia Nkem; Aigbiremhon, Jennifer Airiarebhe (Quantitative Economics and Management Studies, 2025)
Leadership styles are widely acknowledged as a fundamental factor in determining organizational success, influencing the performance of employees and the overall organizational culture. How leaders manage their teams can greatly impact employee attitudes, motivation, and behaviours, affecting productivity, job satisfaction, and organizational commitment. Using an online survey, this quantitative study employed data collected from 373 staff members at a Manufacturing Company in Southeast Nigeria. The data collected was analyzed using SPSS version 20. Correlation and regression analyzes were conducted to test the relationship and impact among the variables. The findings highlighted the positive influence of democratic, transactional, autocratic, and transformational leadership on employee attitude. Furthermore, significant values were obtained for the correlation and effect between the constructs (p < 0.05). Therefore, adopting a multiple approach is recommended in leadership, rather than a singular style when dealing with employees in an organization.